Renewable energy sources in the Lubusz Voivodship (Poland). The present conditions and perspectives for development = Odnawialne źródła energii w województwie lubuskim (Polska). Stan obecny i perspektywy rozwoju - Łączak, Andrzej; Bazan-Krzywoszańska, Anna; Mrówczyńska, Maria; Skiba, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the present situation in terms of energy production from renewable energy sources and perspectives for development, based on research on the existing resources and possibilities of using them. The Lubusz Voivodeship is not an important energy producer in Poland. In terms of the amount of energy produced it comes twelfth out of sixteen voivodeships. The annual energy production from renewable energy sources is 290,9 GWh, which is 11.6% of the total energy produced.
Keywords: renewable energy sources; RES; Lubusz Voivodeship; odnawialne źródła energii; OZE; Lubuskie